Key Techniques and Risk Management for the Application of the Pile-Beam-Arch (PBA) Excavation Method: A Case Study of the Zhongjie Subway Station. (9th April 2014) - Guan, Yong-ping; Zhao, Wen; Li, Shen-gang; Zhang, Guo-bin
Abstract : The design and construction of shallow-buried tunnels in densely populated urban areas involve many challenges. The ground movements induced by tunneling effects pose potential risks to infrastructure such as surface buildings, pipelines, and roads. In this paper, a case study of the Zhongjie subway station located in Shenyang, China, is examined to investigate the key construction techniques and the influence of the Pile-Beam-Arch (PBA) excavation method on the surrounding environment. This case study discusses the primary risk factors affecting the environmental safety and summarizes the corresponding risk mitigation measures and key techniques for subway station construction using the PBA excavation method in a densely populated urban area.